Modeling And Detecting Of Outlier Values In The Saudi Stock Exchange - Abdullah M, Rashedi Khudhayr (2023)
This thesis focuses on the problem of detecting and correcting outliers in the Saudi Arabia stock market (Tadawul) datasets. The aim is to identify such outliers by adopting two approaches.